2012
DOI: 10.7763/ijcee.2012.v4.489
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Using Finger Tip Temperature: FirstStep towards an Automatic System

Abstract: Abstract-clinically, finger tip temperature (FTT) has been used as a sensitive index to monitor if a person is relaxed or not. When a person is relaxed, his/her vessels will be dilated and finger tip will be warmer. If one is anxious or tense, the vessels will be constricted and finger tip will be cool. FTT is a method of bio-feedback to tell the patient if he/she is in a relaxed condition. The subjects experiencing emotion in a higher magnitude differ from those who can regulate the emotions and such a factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We have provided an example of a typical signal trace in Figure 1. FTT has been used to monitor if a person is relaxed or not (Shivakumar, 2012). For our experiments, we used an original device which includes a thermocouple and original circuitry to measure FTT.…”
Section: Physiological Data and Experimental Equipmentmentioning
confidence: 99%
“…We have provided an example of a typical signal trace in Figure 1. FTT has been used to monitor if a person is relaxed or not (Shivakumar, 2012). For our experiments, we used an original device which includes a thermocouple and original circuitry to measure FTT.…”
Section: Physiological Data and Experimental Equipmentmentioning
confidence: 99%
“…In detail, the video stimuli presented a thriller scene and the temperature decreased during this stimuli. The same principle has been recently adopted with fingertip temperature to implement first steps toward an automatic recognition system [22].…”
Section: Electrophysiology and Emotionsmentioning
confidence: 99%
“…Although the research on physiological information abroad originated in the last century, it is very rare to study physiological information and motion recognition at the same time. In addition, in the last century, foreign scholars have found that the reduction of HRV can cause some mental diseases [5] , Skin temperature can be used to identify whether a person is relaxed or not [6] , and the change of pupil diameter can be used as a sensitive and useful indicator of mental state [7][8] . However, although the research on physiological information abroad originated from the last century, it is very rare to study physiological information and motion recognition at the same time.…”
Section: Introductionmentioning
confidence: 99%